An optional macro-economic planning model for the Bangladesh economy : strategies for self-reliant development - Haque, Wahidul; Rahman, Sultan Hafeez; Bangladesh Institute of Development Studies (Dhaka : Bangladesh Institute of Development Studies, 1988)
This study was initiated in 1984, designed to create a planning for self-reliance for the Economy of Bangladesh
Includes bibliographical references.
asm 22/01/2019
Loans
Keywords: Economic policy--Econometric models; Economic policy---Mathematical models; Bangladesh